2017
DOI: 10.1080/13651501.2017.1297834
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine augmentation rapidly improves depression scores in inpatients with treatment-resistant bipolar depression

Abstract: The results confirm a rapid antidepressant effect of ketamine infusion in a considerable proportion of those patients with bipolar depression receiving mood-stabilising drugs. Apart from male gender, no other clinical factors were predictors of response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 22 publications
0
26
0
1
Order By: Relevance
“…Our findings bear directly upon discrepancies in the literature whether ketamine has greater, lesser, or no different effect in men and women. The day of injection might greatly influence the acute benefits of ketamine and differences in treatment timing might explain the great variability (anywhere from 40 to 80%) across clinical trials, including a recent report of only 43% of women showing improvement after ketamine infusion [76]. Increased understanding of these mechanisms with regard to sex differences will help develop tailored therapies and identify new risk and/or protective factors for psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings bear directly upon discrepancies in the literature whether ketamine has greater, lesser, or no different effect in men and women. The day of injection might greatly influence the acute benefits of ketamine and differences in treatment timing might explain the great variability (anywhere from 40 to 80%) across clinical trials, including a recent report of only 43% of women showing improvement after ketamine infusion [76]. Increased understanding of these mechanisms with regard to sex differences will help develop tailored therapies and identify new risk and/or protective factors for psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Patients treated with ketamine were medication-free in some studies 6,31 ; ongoing medications were continued unchanged in others. 8,32 In this context, a suggestion that psychiatrists can consider is to continue necessary antidepressant and other medications during a ketamine trial, especially because maintenance antidepressant treatment will be required should the patient respond or remit. With specific reference to diagnostic subgroups, patients could need mood stabilizer and/or antipsychotic medication when the illness being treated is bipolar depression or depression with psychotic symptoms.…”
Section: Parting Notes: Use Of Concurrent Medications During a Ketamimentioning
confidence: 99%
“…13 In an open-label study of 42 patients with bipolar depression, Permoda-Osip et al found that 52% responded to a single infusion of ketamine; 14 the rapid antidepressant effect was replicated in a subsequent study conducted among 53 patients with bipolar depression. 15 In another study, 23 and 4 patients with unipolar and bipolar depression, respectively, were administered esketamine (0.25mg/ kg); almost half of the patients (48.1%) showed a response within 1 week of treatment. Ten patients (37.0%) experienced remission in the same period.…”
Section: Introductionmentioning
confidence: 99%